THE ROLE OF TRAINING AND HUMAN RESOURCE DEVELOPMENT IN INCREASING WORK PRODUCTIVITY IN REZEKY KEBAYA MICRO ENTERPRISES: PERAN PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN PRODUKTIVITAS KERJA DI USAHA MIKRO REZEKY KEBAYA - Wulandari, Siti (LPPM UPMI, 2024)
In the era of globalization and increasingly tight business competition, human resource (HR) development is a key factor in achieving company success and competitiveness, including in the micro business sector. The method in this research uses a descriptive qualitative approach with a case study method on the Rezeky Kebaya Fashion microenterprise. This research is descriptive qualitative research. Data was collected through interviews with business owners and employees, as well as direct observation of the workplace. The results of this research show that structured research and developing employee skills have a significant influence on increasing work productivity, which is reflected in increasing product quality and working time efficiency. Ongoing training also contributes to increasing employee motivation. Training and development of human resources (HR) has a crucial role in increasing work productivity in micro businesses such as Rezeky Kebaya. By providing relevant training and development opportunities for employees, micro-enterprises can optimize their abilities and skills, which in turn has a positive impact on work efficiency and product quality. Based on the results of this research, it is recommended that other micro businesses implement similar HR development programs to achieve increased productivity